Multilevel Analysis on the Determinants of Antenatal Care Visit at Community Health Center in Madiun, East Java - Purbaningrum, Sinta Ayu; Qadrijati, Isna; Adriani, Rita Benya; Prasetya, Hanung (Journal of Maternal and Child Health, 2019)
Background: Antenatal care (ANC) is an important determinant of high maternal mortality rate and one of the basic components of maternal care. However, some pregnant women still had low awareness about the importance of ANC. The purpose of this study was to examine determinants of ANC visit in community health center, Madiun, East Java, and to determine the contextual effect of the community health center on the ANC visit. Subjects and Method: This was a case-control study conducted in Madiun, East Java, from November to December 2018. A sample of 200 pregnant women was selected by simple random sampling. The dependent variable was ANC visit. The independent variables were knowledge, occupation, number of children, attitude, income, and husband support. The data were collected by questionnaires and analyzed by a multilevel linear regression. Results: The likelihood of ANC visit increased with employment status (b= 1.97; 95% CI= 0.81 to 3.13; p= 0.001), good knowledge (b= 1.56; 95% CI= 0.41 to 2.72; p= 0.008), positive attitude (b= 1.74; 95% CI= 0.52 to 2.96; p= 0.005), higher family income (b= 1.42; 95% CI= 0.29 to 2.55; p= 0.014), and stronger husband support (b= 1.29; 95% CI= 0.16 to 2.43; p= 0.260). ANC visit decreased with larger number of children (b= -1.05; 95% CI= -2.17 to 0.07; p= 0.067). Community health center had strong contextual effect on ANC visit in pregnant women with ICC= 41.85%. Conclusion: ANC visit increases with employment status, good knowledge, positive attitude, high family income, and strong husband support. ANC visit decreases with large number of children. Community health center has strong contextual effect on ANC visit in pregnant women. Keywords: antenatal care, determinants, pregnant women Correspondence: